MENINGKATKAN KETERAMPILAN SOSIAL ANAK USIA 4-5 TAHUN MELALUI KEGIATAN COOPERATIVE PLAY DI TK KEMALA BHAYANGKARI 55 SURAKARTA - Rilla, Yesa; Feri Faila Sufa; Oka Irmade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the social skills of children aged 4-5 years through the implementation of the cooperative play method. The research employed a mixed-method approach (qualitative and quantitative) using Classroom Action Research (CAR) based on Kurt Lewin’s model, conducted in two cycles. The subjects were 15 children in Group A at TK Kemala Bhayangkari 55 Surakarta in the 2025/2026 academic year. Data were collected through observation, interviews, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results showed a significant improvement in children’s social skills after the implementation of cooperative play. In the pre-cycle stage, most children were in the undeveloped category (40%). In Cycle I, improvement began to appear but was not yet optimal, with 40% achieving good and very good categories. After improvements in Cycle II, the percentage increased to 80%, meeting the success criteria. The improvement was evident in children’s abilities to cooperate, communicate, share, take turns, and follow rules. Therefore, the cooperative play method is proven effective in enhancing early childhood social skills through collaborative and interactive play activities.